The Effect of the Rebozo Technique on the Length of the First Stage in Vaginal Labor - Putri Habibah; Lisa Trina Arlym (Newinera Publisher, 2026)
The first stage of labor is often associated with prolonged duration, pain, and maternal discomfort, which may increase the risk of obstetric interventions. Non-pharmacological approaches are increasingly promoted to support physiological labor. The Rebozo technique, a traditional method originating from Latin America, has gained attention for its potential to improve labor progress by enhancing pelvic mobility and fetal positioning. This study aimed to systematically review the effect of the Rebozo technique on the duration of the first stage of vaginal labor. A systematic literature review was conducted following PRISMA guidelines. Articles were retrieved from ProQuest, PubMed, SpringerLink, and ScienceDirect databases using the keywords “Rebozo technique,” “vaginal delivery,” and “first stage of labor.” Inclusion criteria were based on the PICOS framework, focusing on primigravida women undergoing vaginal delivery. Only quantitative studies and randomized controlled trials published between 2020 and 2025 were included. Methodological quality was assessed using the Center for Evidence-Based Medicine (CEBM) critical appraisal tool. Five high-quality studies from four countries met the inclusion criteria. The findings consistently demonstrated that the Rebozo technique was associated with a shorter duration of the first stage of labor, improved cervical dilation, enhanced fetal head rotation, and increased maternal comfort. The Rebozo technique is a safe and effective non-pharmacological intervention that supports labor progression and maternal well-being. Its integration into midwifery practice may optimize the management of the first stage of vaginal labor.